DETERMINAN PERILAKU PENGELOLAAN KEUANGAN MAHASISWA: SUATU MODEL MODERASI DAN MEDIASI - Nurhayati, Ulfa Syaroh; Aeni, Ida Nur (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study aims to analyze and provide empirical evidence related to the influence of social comparison orientation and spiritual intelligence on financial management behavior with financial self-efficacy as a mediating variable and financial socialization as a moderation variable. This study uses a quantitative approach with primary data sources. There were 251 students of the Accounting Education Study Program as respondents. The data of this study was analyzed using SEM-PLS. The results show that social comparison orientation does not directly affect financial management behavior. In contrast, spiritual intelligence, financial self-efficacy, and financial socialization influence financial management behavior. Financial self-efficacy mediates the influence of social comparison orientation and spiritual intelligence on financial management behavior. However, financial socialization does not moderate the relationship. The results of this study provide implications for policy formulation in encouraging better and sustainable financial management.